Wind Atlas as a Social and Productive Tool for Farmers in the Municipality of Santander de Quilichao - Martínez Romero, Ever Gregorio; Matallana, Edgar (I+ T+ C- Research, Technology and Science, 2025)
The project "Wind Atlas as a Social and Productive Tool for Farmers in the Municipality of Santander de Quilichao” is an initiative by the Corporación Universitaria Comfacauca UNICOMFACAUCA, aimed at providing small and medium-sized farmers a key tool for climate-smart decision-making. The project’s main purpose is to develop a Wind Atlas for the municipality of Santander de Quilichao. To this end, four low-cost meteorological stations were installed to collect precise data on wind speed and direction. The stations were interfaced via Wi-Fi to the Weather Wunderground platform, which allowed real-time access to the collected data. The data was then downloaded as a CSV file and filtered using Excel and Python. The filtered information was used with the WRPLOT View program to generate a wind rose for each station. Using both elements: Wind roses and QGIS program, the wind atlas of the municipality was generated.